LITERATURE REVIEW: FACTORS AFFECTING FINAL YEAR STUDENTS' ANXIETY IN PREPARING A THESIS IN INDONESIA - Ania Al Izza; Syifaul Lailiyah (Journal of Community Mental Health and Public Policy)
Background: Thesis or final project is often used as a graduation requirement by most campuses in Indonesia. Writing a thesis is often considered terrifying because students often experience difficulties. This triggers anxiety and even depression for final year students for fear of not being able to complete their thesis writing. Purpose: To find out the factors that influence the anxiety of final year students in preparing a thesis. Methods: Literature study research using national articles with published years 2018-2023. Articles were searched using the Preferred Reporting Items for Systematic Reviews & Meta-Analyses (PRISMA) method. Inclusion criteria included publication of articles reviewed no more than the last ten years, titles still related to keywords, quantitative or qualitative research, and full text. Exclusion criteria were articles published more than ten years, titles not related to keywords, and inaccessible. Database using google scholar. Results: Factors that influence the anxiety of final year students in preparing a thesis come from internal and external factors. Conclusion: Internal factors, such as lack of self-confidence, self-efficacy, self-discipline, fighting power, self-control, and high perfectionism. External factors, such as supervising lecturers, lack of parental and family support, and peer support.